Collaborative Governance to achieve Village SDGs: A Case Study of Irrigation Systems in Krandegan Village - Ambang Aries Yudanto; Akhmad Solikin; Isna Windani (INOBIS: Jurnal Inovasi Bisnis dan Manajemen Indonesia, 2024)
Krandegan Village strives to create a clean and renewable energy village, with one of the major programs is the transition from a diesel powered-irrigation system to a solar powered-irrigation system to achieve Village SDGs. This study aims to elaborate the collaborative governance among stakeholders involved within the village. The stakeholders’ identification is based on Penta Helix perspective. The influential parties are the Village Government, the Business World, Universities, Non-Governmental Organizations, and the Mass Media. The role of the Village Government is to be an orchestrator to integrate existing stakeholders to jointly build the Village in a collective and inclusive way. The business world plays a role in providing resource support, especially the material to support the sustainability of the village irrigation system. The University contributes ideas and roles through research approaches and community service carried out by lecturers and students. NGOs function by managing donations from donors, maintaining the sustainability of supporting infrastructure for the village irrigation system, and coordinating the governance process of the irrigation system. Mass Media plays a role in delivering positive news and information related to Village to the public. Furthermore, parties within Krandegan Village can generally put Ratner’s collaborative governance action planning into practice.